Digital Journalism and Public Mass Media: The Bad News - Quiroga, Sergio Ricardo (Brazilian journalism research, 2016)
In this paper we intend to study how police and security information is presented by the News Agency, San Luis. We examined the production of police and security information produced in 2013 by the San Luis News Agency (ANSI), a state news platform created to transmit government information in the province of San Luis, Argentina in 2012. The initiatives and progress for the people in police and security matters in the mass media, has a material-functional dimension, referring exclusively to improving the detachments, the delivery of police vehicles, and operational controls. That vision is diffused by the state agency for information and does not contribute to the promotion of ideas and discussions on citizen participation in security policies and the development of democracy.